Pengaruh Absensi Online Terhadap Disiplin Kerja Pegawai Pada Kantor Kecamatan Tamalate Kota Makassar - Syam, Andi Hendra; Dina, Novita; Monalisa (Forum Cendekia: Jurnal Ilmiah Multidisipliner, 2024)
This research aims to determine the effect of online attendance on employee work discipline at the Tamalate sub-district office, Makassar City. The object of this research is the Tamalate sub-district office, Makassar City. In this research, the method used by the author is a quantitative method. The sample in this research is all State Civil Apparatus Staff in the Tamalate District Head's office who are also 80 respondents. The results of this research have been tested for validity and reliability. The data analysis technique uses simple linear regression analysis with hypothesis testing. The results of this research show that there is a positive and significant influence of the Online Attendance variable (X) on the Work Discipline variable (Y), meaning that by implementing good online attendance, employee work discipline will also be good.